Theories of the New Class : intellectuals and power - King, Lawrence P.; Szelényi, Iván (Contradictions (Minneapolis, Minn.), 2004)
In Theories of the New Class, Iván Szelényi, one of the most incisive and respected analysts of the intellectual class, and Lawrence King put New Class theories into a broad historical framework for the first time. This book grounds class theories in contemporary issues, and uses modern polemics to revitalize historical debates on the origins of capitalism.